Artificial intelligence and the law - Bruyne, Jan de; Vanleenhove, Cedric (Cambridge : Intersentia, 2021)
Artificial intelligence (AI) is becoming more increasingly prevalent in our daily social and professional lives. Although AI systems and robots bring many benefits, they present several challenges as well. In this comprehensive book, scholars critically examine how AI systems may impact Belgian law. It contains contributions on consumer protection, contract law, liability, data protection, procedural law, insurance, health, intellectual property, arbitration, lethal autonomous weapons, tax law, employment law and ethics. While specific topics of Belgian private and public law are thoroughly addressed, the book also provides a general overview of a number of regulatory and ethical AI evolutions and tendencies in the European Union. Therefore, it is a must-read for legal scholars, practitioners and government officials as well as for anyone with an interest in law and AI.
Title from publisher's bibliographic system (viewed on 28 May 2021).
Keywords: Artificial intelligence -- Law and legislation